Good isometric and isokinetic power restoration after distal biceps tendon repair with anchors - Höppchen, Arnold; Grützner, Paul Alfred; Tinelli, Marco (Archives of orthopaedic and trauma surgery, 2017)
Introduction: Distal biceps brachii tendon rupture can lead to 30-40% power loss of elbow flexion and up to 50% of forearm supination. Re-fixation of the distal biceps brachii tendon is recommended to warrant an adequate quality of the patient’s life. This study reports the isometric and isokinetic results after anchor re-fixation 2.5 years after surgery. Patients and methods: Between 2007 and 2010, 69 patients with distal biceps brachii tendon tear underwent a suture anchor reattachment. During the follow-up examination, a questionnaire and DASH score were filled in, the circumferences of the arm were measured, range of motion was collected, and different trials were conducted at the BTE Primus RS™ (Baltimore Therapeutic Equipment) on both arms. Results: 49 patients (71%) were reinvestigated with a follow-up of 32 months (11-58 months). A significant difference was found in the ability of elbow flexion between the affected arm and the opposite side as well as in pronation and supination. In elbow flexion and extension as well as in pronation and supination of the forearm, the strength was significantly diminished. Conclusions: 32 months after surgical re-fixation of the distal biceps brachii tendon rupture, strength in all exercises is marginally reduced in comparison to the opposite arm. Re-fixation of the distal biceps brachii tendon is an adequate method to return the range of motion and the strength in the elbow joint to an almost normal level and that gives rise to a high level of patient satisfaction. Level of evidence: Level III, case-control study.